MAKNA TEOLOGIS YESUS “MELEWATI” SEBAGAI RESPONS GEREJA BAGI #INDONESIAGELAP – KONTEKSTUALISASI MARKUS 6:45-52 MENGGUNAKAN MODEL BUDAYA TANDINGAN - Ronny (STT IKSM SANTOSA ASIH, 2025)
Abstract The hashtag “Dark Indonesia” (or “Indonesia C[E]mas” as an irony of “Indonesia Emas”) has become very popular as a representation of anxiety on social media because of the political, economic, social and cultural context that is considered to be heading towards decline or deterioration in our country. The people of God, as part of this country, must certainly be part of the solution. But what is the truth of the Gospel as a reflection and basis for taking action? This article explores the word “passing” in Mark 6:45-52 and two passages of the Bible in the Old Testament to bring out the original meaning and message of God's word for His people in the midst of the problematic situations and conditions in general in Indonesia today. This article does not aim to produce practical and final solutions to all or one of the problems in a particular field, but by using the contextual theology model of Stephen Bevans' Counterculture, this article attempts to produce a contextual theological message that is expected to be a means by the Holy Spirit to provide comfort, perseverance and illumination for readers of this article and apply the message and contribute to our country. The exploration of theological messages is carried out through a literature study approach with primary sources from the Bible text regarding the word